REPRODUCTIVE HEALTH APPS AND EMPOWERMENT – A CONTRADICTION? - Tylstedt, Beatrice; Sadowski, Helga; Eklund, Lina; Normark, Maria (AoIR Selected Papers of Internet Research, 2023)
FemTech apps have billions of users globally. Yet, despite their popularity, we know little about these apps, often developed outside controlled and regulated healthcare. While these apps have been criticised for lacking privacy and for enforcing normative ideals on women, they are often marketed in terms of female empowerment. In this presentation, we present our analysis of the empowering potential of menstruation and pregnancy apps. We ask: How do these apps represent reproductive health? What kinds of empowering qualities are present in them? Are there any aspects of the technology that (inadvertently) counteract the empowering purpose? We investigate this through a comparative design investigation using what we call critical app-walkthrough methodology together with researcher use-diaries. We show in our analysis that there are three critical ways in which these apps represent reproductive health events to users through design. We analyze; 1) interface metaphors used to represent temporality, 2) datafication of reproductive health through input and output for intimate data tracking and 3) finally the ways predictions convey certainty over uncertainty and the implications of this. From our results, we present four design sensitivities meant to inspire designers to design for other types of period tracking experiences that might better empower bleeders; support lived temporalities, embrace uncertainty, empower the self, and design less.